1982
DOI: 10.1021/ac00243a028
|View full text |Cite
|
Sign up to set email alerts
|

Secondary ion mass spectrometry of protected diribonucleoside monophosphates with a time-of-flight mass spectrometer

Abstract: Positive and negative secondary Ion mass spectra have been measured for eight fully protected diribonucleoside monophosphates with various permutations of bases and protecting groups. The spectra, produced by 8-28 keV Cs+ Ions, were examined In a tlme-of-fllght mass spectrometer. The spectra yield a wealth of diagnostically useful Information enabling determination of the molecular weight, Identification of the protecting groups present, Identification of the nucleobases present, and determination of the base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…For example, field desorption (FD) (2, 3), desorption chemical ionization (DCI) (4), thermospray (5), and liquid ionization (6) have been successfully used for the analysis of nonderivatized nucleosides and nucleotides. More recently impressive results on polar, nonvolatile organic molecules have been demonstrated using a group of particle-induced desorption ionization techniques, e.g., secondary ion mass spectrometry (SIMS) (7,8), 252Cf plasma desorption mass spectrometry (PDMS) (9)(10)(11), laser desorption (LD) (12), and fast atom bombardment mass spectrometry (FAB-MS) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…For example, field desorption (FD) (2, 3), desorption chemical ionization (DCI) (4), thermospray (5), and liquid ionization (6) have been successfully used for the analysis of nonderivatized nucleosides and nucleotides. More recently impressive results on polar, nonvolatile organic molecules have been demonstrated using a group of particle-induced desorption ionization techniques, e.g., secondary ion mass spectrometry (SIMS) (7,8), 252Cf plasma desorption mass spectrometry (PDMS) (9)(10)(11), laser desorption (LD) (12), and fast atom bombardment mass spectrometry (FAB-MS) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…If there is a kinetic isotope effect associated with the ionic fragmentaion (as there usually is) then these coefficients will not be equal ( a # /3). Substituting eq 10a and 10b into eq 9 for the mole fractions of the isotope variants of the split fragment ion, X V ) i k , and rearranging give the result Mi = MO + N;((mH -mL) + aM(n)L -PM(n)H} (11) where M (~) L and M (~) H represent the average masses for the neutral fragments eliminated in forming the light and heavy isotopic forms of the fragment ions. Note that since a and /3 are constants for a given material under a given set of experimental conditions, the collection of terms within the braces is also a constant.…”
Section: Xkx(f)ik) and Rearranging Givementioning
confidence: 99%
“…Since the solution to the average mass equation is direct and exact for compounds with complex naturally occurring isotopic distributions, this method may be ideally suited to the isotopic analyses of materials which contain polyisotopic elements (such as inorganic and organometallic compounds). Work in other laboratories has demonstrated that it is pmsible to measure the average mass of an isotopic cluster precisely even at high mass (8) and when the peaks in the cluster are not resolved (9)(10)(11). Consequently, the average mass approach could eventually prove useful in the isotopic analyses of high molecular weight samples and those which require the use of mass spectral methods which cannot provide unit mass resolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We could not obtain protonation or deprotonation under any experimental conditions. Plasma desorption mass spectrometry has been shown by McNeal et al 13 and secondary ion mass spectrometry (SIMS) by Ens et d 3 and Beavis et all4 to have advantages in this area. Our next objective was to check out fully protected dinucleotides, where one of the protection groups is missing, namely the end phosphate, which is protected normally with tribromoethyl or cyanoethyl.…”
mentioning
confidence: 99%